A case of radiation cataract found 29 years after radiation exposure - Pasyechnikova, N. V.; Fedirko, P. A.; Babenko, T. F. (Ukrainian Journal of Ophthalmology, 2025)
Background: Radiation cataracts are an acknowledged biological effect of radiation exposure. It has been demonstrated previously that, the mode value for the latent period for the identified post-Chornobyl cases of radiation cataract was 9 years. We present a case of radiation cataract with typical clinical features that manifested 29 years after radiation exposure. Material and Methods: A female patient, born in 1937, worked in the exclusion zone of the Chornobyl Nuclear Power Plant in early May of 1986; she is now under our regular supervision. Because over years, the patient had had the annual routine eye examination (including, but not limited to biomicroscopy, lens examination and red reflex photography using a fundus camera), the time of onset of specific lens opacity could be placed within a period of several months. Results: On examination performed on December 15, 2014, the right lens showed mild peripheral cortical opacity without signs of radiation cataract, and with vacuoli seen in the anterior subcapsular lens region. On examination performed on August 8, 2015, the right eye showed a mild, specific, posterior, central subcapsular opacification. Conclusion: We presented a case of radiation cataract, documented by fundus camera photography, with typical clinical features that manifested 29 years after radiation exposure. Detecting a radiation cataract so late after radiation exposure indicates that the changes in the eye exposed to radiation can be very durable.